2021
DOI: 10.3390/ijerph18158051
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment and Coordination Characteristics of Production, Living, Ecological Function—A Case Study of Henan Province, China

Abstract: Multifunctional state assessment was the basis of time sequence design of territory spatial development and overall utilisation. This study aimed to identify the ecological-production-living (PLE) territory spatial function to provide a basis for territory spatial planning. It took Henan Province as the research area. This study developed a methodology to assess differentiation characteristics for PLE function, a method that integrates functional merging and geographic information technology. We used the coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…During rapid urbanization and industrialization, land-use transitions may directly or indirectly impact regional ecoenvironments, leading to derived eco-environmental effects (Foley et al, 2005;Lambin and Meyfroidt, 2011;Zhang et al, 2011;Haas and Ban, 2014;Hu et al, 2016;Quintas-Soriano et al, 2016;Allington et al, 2017;Hanaõcek and Rodríguez-Labajos, 2018;Li et al, 2020;Long et al, 2020;Tian et al, 2020). The concept of production-living-ecological space (PLES) was first proposed in the report of the 18th National Congress of the Communist Party of China in 2012 (Hu, 2012), which stressed that "the production space should be intensive and highly efficient, the living space should be moderate and livable, and the ecological space should be unspoiled and beautiful" (Sun et al, 2020;Wang et al, 2020;Fu and Zhang, 2021). Research on land-use transitions and eco-environmental effects from the perspective of PLES is an important basis for optimizing the rational allocation of land resources and for constructing an ecological civilization, which has become a major topic in current research (Li et al, 2016;Liu et al, 2017;Asadolahi et al, 2018;Luo et al, 2018;Hu M. et al, 2019;Hu S. et al, 2019;Lou et al, 2019;Asabere et al, 2020;Tan et al, 2020;Xie et al, 2021;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…During rapid urbanization and industrialization, land-use transitions may directly or indirectly impact regional ecoenvironments, leading to derived eco-environmental effects (Foley et al, 2005;Lambin and Meyfroidt, 2011;Zhang et al, 2011;Haas and Ban, 2014;Hu et al, 2016;Quintas-Soriano et al, 2016;Allington et al, 2017;Hanaõcek and Rodríguez-Labajos, 2018;Li et al, 2020;Long et al, 2020;Tian et al, 2020). The concept of production-living-ecological space (PLES) was first proposed in the report of the 18th National Congress of the Communist Party of China in 2012 (Hu, 2012), which stressed that "the production space should be intensive and highly efficient, the living space should be moderate and livable, and the ecological space should be unspoiled and beautiful" (Sun et al, 2020;Wang et al, 2020;Fu and Zhang, 2021). Research on land-use transitions and eco-environmental effects from the perspective of PLES is an important basis for optimizing the rational allocation of land resources and for constructing an ecological civilization, which has become a major topic in current research (Li et al, 2016;Liu et al, 2017;Asadolahi et al, 2018;Luo et al, 2018;Hu M. et al, 2019;Hu S. et al, 2019;Lou et al, 2019;Asabere et al, 2020;Tan et al, 2020;Xie et al, 2021;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the “three-line” management and control of the PLES layout should be optimized to build a high-quality territorial spatial development pattern. Based on the zoning of the main functional zones, the types of main functional zones should be defined in each region to promote high-level coupling and coordination of PLES [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building a scientific and reasonable classification system of PLES is the premise and basis for studying the structural evolution of PLES [ 44 ]. Territorial spatial pattern is a comprehensive reflection of the interaction and coupling between natural ecological process and humanistic social system [ 45 ], and territorial space is a multi-functional complex [ 18 , 34 , 46 , 47 ]. Scholars have conducted a large number of studies on the classification of PLES, mainly based on the dominant functions of different land use types [ 5 , 44 ].…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…Pieces of previous research have been conducted on the MFZ, mainly focusing on the conceptual theory [ 10 , 14 , 15 , 16 ], zoning [ 17 ], structural analysis [ 15 ], monitoring and evaluation [ 5 , 18 ], simulation [ 19 , 20 , 21 ], coordinated development [ 5 , 7 , 22 ], pattern optimization [ 23 , 24 , 25 , 26 ], influence mechanism [ 5 , 27 ], and supporting policies [ 28 ]. As the strategic background of national planning, the MFZ is the prospect of the overall pattern of China’s territorial spatial protection and development in the future [ 11 , 14 ], which can guide the quantity distribution and spatial layout of production-living-ecological space (PLES) through territorial spatial planning, three-zones and three-lines management and control [ 11 ].…”
Section: Introductionmentioning
confidence: 99%